Knockout of the primary sclerosing cholangitis‐risk gene Fut2 causes liver disease in mice. Issue 2 (19th June 2017) - Maroni, Luca; Hohenester, Simon D.; van de Graaf, Stan F.J.; Tolenaars, Dagmar; van Lienden, Krijn; Verheij, Joanne; Marzioni, Marco; Karlsen, Tom H.; Oude Elferink, Ronald P.J.; Beuers, Ulrich
Abstract : The etiopathogenesis of primary sclerosing cholangitis is unknown. Genetic variants of fucosyltransferase 2 (FUT2) have been identified in genome‐wide association studies as risk factors for primary sclerosing cholangitis. We investigated the role of Fut2 in murine liver pathophysiology by studying Fut2 –/– mice. Fut2 –/– mice were viable and fertile, had lower body weight than wild‐type (wt) littermates and gray fur. Half of the Fut2 –/– mice showed serum bile salt levels 40 times higher than wt ( Fut2 –/– high ), whereas the remainder were normocholanemic ( Fut2 –/– low ). Fut2 –/– mice showed normal serum liver tests, bile flow, biliary bile salt secretion, fecal bile salt loss, and expression of major hepatocellular bile salt transporters and cytochrome P450 7a1, the key regulator of bile salt synthesis, indicating that elevated serum bile salts in Fut2 –/– high mice were not explained by cholestasis. Fut2 –/– high mice, but not Fut2 –/– low mice, were sensitive to hydrophobic bile salt feeding (0.3% glycochenodeoxycholate); they rapidly lost weight and showed elevation of serum liver tests (alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase) and areas of liver parenchymal necrosis. Histomorphological evaluation revealed the presence of paraportal shunting vessels, increased numbers of portal vascular structures, wall thickening of some portal arteries, and periductal fibrosis in Fut2 –/– high mice more than Fut2 –/– low mice and not wt mice. Unconjugated bilirubin and ammonia were or tended to be elevated in Fut2 –/– high mice only. Portosystemic shunting was demonstrated by portal angiography, which disclosed virtually complete portosystemic shunting in Fut2 –/– high mice, discrete portosystemic shunting in Fut2 –/– low mice, and no shunting in wt littermates. Conclusion : Liver pathology in Fut2 –/– mice is dominated by consequences of portosystemic shunting resulting in microcirculatory disturbances, mild (secondary) periductal fibrosis, and sensitivity toward human bile salt toxicity. (Hepatology 2017;66:542–554).